Enhancing Local SMEs through Village-Owned Enterprises: A Case Study in Indonesia - Eny Maryanti; Sarwenda Biduri; Herlinda Maya Kumala Sari; Luluk Putri Fauziah (Universitas Muhammadiyah Sidoarjo, 2023)
This article presents a community engagement initiative (abdimas) as part of Higher Education's Tri Dharma, conducted in Lemujut Village, Krembung District, Sidoarjo Regency, East Java. The project focuses on empowering Micro, Small, and Medium Enterprises (MSMEs) by leveraging the Village-Owned Enterprise (Bumdes) as a Distribution Center for local products. Through direct interaction and knowledge dissemination about the Distribution Center concept, the aim is to amplify the visibility and market reach of Lemujut Village's MSME products, fostering competitiveness in the national and global markets while enhancing the local economy. The program employed direct interviews and questionnaires for information dissemination, leading to positive outcomes where Lemujut Village's MSMEs expressed willingness to collaborate with Bumdes as their partner. This study contributes to strengthening MSMEs and Bumdes collaboration models, offering insights for sustainable community development. Highlight: Holistic Community Engagement: This article outlines a higher education community engagement initiative (abdimas) targeting Micro, Small, and Medium Enterprises (MSMEs) in Lemujut Village, leveraging the Village-Owned Enterprise (Bumdes) as a pivotal Distribution Center for local products. Enhancing Visibility and Competitiveness: By disseminating knowledge about the Distribution Center concept and facilitating direct interactions, the project aims to enhance market reach and competitiveness of Lemujut Village's MSME products on national and global platforms, concurrently contributing to the local economy. Collaboration and Sustainability: Employing direct interviews and questionnaires, the study demonstrates successful outcomes, showcasing willingness among Lemujut Village's MSMEs to collaborate with Bumdes. The findings enrich models of MSMEs and Bumdes collaboration, offering valuable insights for fostering sustainable community development. Keyword: Community Engagement, MSMEs Empowerment, Village-Owned Enterprise (Bumdes), Distribution Center, Sustainable Development